Improving hypertext navigation map usability through graphic differentiation techniques - Padovani, Stephania; Velozo, Janayna (InfoDesign, 2007)
The usability of a system is defined as its capability of being used easily and effectively by a specific range of users to perform a specific range of tasks within a specific range of environments. Aiming to investigate the effects of graphic differentiation techniques upon site map usability, this article summarises the results of three experimental studies, when three different versions of a site map were tested with sixty users. Initially, a map without differentiation was tested and users interviewed. In the second phase, a map with colour coding was tested, which was followed by the tests involving a map with pictorial differentiation. Results demonstrated several benefits of the application of differentiation techniques in terms of performance and user satisfaction.